Evaluation of cervical cancer screening program implementation in Boyolali District in 2024 - Amira Nada Fatikha; Shinta Prawitasari; Riris Andono Ahmad; Teguh Tri Kuncoro (Berita Kedokteran Masyarakat, 2025)
Purpose: The Boyolali district has never reached the cervical cancer screening coverage target for women of childbearing age, aged 30-50 years. In 2023, cervical cancer screening coverage reached 1.7% of the target of 63%. So this study aims to evaluate the implementation of the cervical cancer screening program in Boyolali District in 2024. Methods: This study used a descriptive, observational, quantitative design, with analysis using a logic model that included the program implementation components of inputs, activities, and outputs. Sampling was purposive, with 28 respondents selected for their roles in the cervical cancer screening program. Primary data were collected using a questionnaire instrument. All data obtained were then processed and analyzed descriptively using Microsoft Excel. Results: The evaluation of the cervical cancer screening program in Boyolali District shows that the input components, particularly regulations and human resources, remain inadequate. In terms of activities, passive and active services, socialization, advocacy, and monitoring and evaluation are still limited. As for cervical cancer screening in Boyolali District in 2024, coverage was only 2.44% of the target, with 6.53% of tests returning positive results. Conclusion: The implementation of the cervical cancer screening program in Boyolali District in 2024 was not optimal. Improvement efforts are needed in regulations, resources, and the intensity of activities to increase screening coverage.